2021
DOI: 10.2486/indhealth.2020-0064
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to bullying behaviours, resilience, and return to work self-efficacy in patients on or at risk of sick leave

Abstract: The study investigated relationships between exposure to bullying behaviours, return to work self-efficacy (RTW-SE) and resilience, and if resilience moderates the bullying-RTW-SE relationship among patients on sick leave or at risk of sick leave due to common mental disorders (CMD). A sample of 675 patients treated in an outpatient clinic was analysed using regressions and moderation analyses by employing SPSS and the Process macro SPSS supplement. The results showed a negative relationship between exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 61 publications
0
2
0
1
Order By: Relevance
“…Additionally, psychosocial factors like anxiety, depression and stress can have a significant impact, leading to delays, problems, or even making it necessary to change jobs [ 79 ]. Individual differences in resilience, coping strategies and self-efficacy are key factors in how they handle the disease and navigate the RTW process [ 80 , 81 ]. Some may adapt more effectively, while others may face challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, psychosocial factors like anxiety, depression and stress can have a significant impact, leading to delays, problems, or even making it necessary to change jobs [ 79 ]. Individual differences in resilience, coping strategies and self-efficacy are key factors in how they handle the disease and navigate the RTW process [ 80 , 81 ]. Some may adapt more effectively, while others may face challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Workplace bullying can take According to numerous studies, being the target of bullying increases the likelihood that one may leave their employment (Monica & Megawati, 2021). Aarestad et al (2021) found that bullying significantly affected employees' intentions to quit their employment since victims of bullying did so more frequently than non-victims over the course of a two-year period.…”
Section: Workplace Bullying As Mediatormentioning
confidence: 96%
“…Resiliens var overraskende nok ikke en beskyttende faktor, selv om personene som rapporterte høy resiliens i utgangspunktet, viste en høyere forventning om å mestre oppgaver og situasjoner på jobben enn personer med lavere resiliens (Aarestad et al, 2021). Funnet er i strid med hva vi kjenner fra stressteorier (f.eks.…”
Section: Resiliensunclassified